Case Report: Floating Elbow with Posterior Shoulder Dislocation - Ibrahim Halil Kafadar; Ibrahim Karaman; Ziya Emre Yalman; Ali Eray Gunay (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2017)
Shoulder dislocations are the most common joint dislocations (%50). Only 2 to 4 percent of these dislocations are posterior dislocations. Posterior dislocation of the shoulder is a rare and commonly missed injury. Also, combination of the fracture of the humerus with shoulder dislocation is a very rare injury [1-6]. Floating elbow is also relatively rare condition and usually high-energy trauma takes place in the etiology. The floating elbow was first described in children by Stanitsky and Micheli in 1980 and then, described in adults in 1984 by Rogers [7,8]. Classical defi nition is about coexistence of the ipsilateral humeral diaphyseal and the forearm fracture. Also, various complications could be seen early and late in cases with floating elbow; compartment syndrome, neurovascular deficiency, limb loss etc. Consequently, floating elbow is a rare but important lesion, with possible long-term complications. Surgical treatment is universally accepted with various techniques [9-11]. In a study which was published by Winderman in 1940, anterior shoulder dislocation associated with the humerus fracture was defi ned [1], but posterior shoulder dislocation with forearm fracture in addition to humerus fracture has not been reported yet.